Training on making kombucha tea from snake fruit peel and butterfly pea flower - Astrilia Damayanti; Megawati Megawati; Widi Astuti; Luluk Arvi Cahyaning Suwandi; Reyhan Dwi Saputra; Melanie Hartalia Putrie (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Snake fruit peel is an organic waste that is often not utilized, while the flower of the butterfly pea is known as a natural dye for food and beverages. The COVID-19 pandemic causes susceptibility to the human body. Therefore, it is necessary to process healthy drinks in order to utilize organic waste. This community service program activity aims to introduce fermented food processing to the community, especially the Family Welfare Development (PKK) Group RT 3 RW 3, Ngijo Village, Gunungpati District, Semarang City by utilizing snake fruit peel (Salacca zalacca) and butterfly pea flower (Clitoria ternatea) as kombucha tea. The method of this program is in the form of delivering material either through posters, videos, demonstrations, and youtube links. A positive response was given by community after conducting a taste test on the product that was socialized in the form of many questions submitted including other alternative raw materials and the volume of kombucha tea served. This program has the potential to foster community motivation in entrepreneurship so that family income will increase.